Hasil Penerapan Asesmen Anak Disgrafia Di Sekolah Inklusi - Suci Angraeni; Delvia Rahmah; Lilis Hermawati; Nadzifa Shafira Putri; Dela Kurnia Agustina; Retno Andriyani (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe and analyze the results of assessment implementation for children with dysgraphia at Sudimara Timur 2 State Elementary School as an inclusive education provider. The research employed a qualitative approach with descriptive case study design involving two dysgraphic students with different characteristics and one special education teacher as key informant. Data collection techniques included in-depth interviews, participatory observation, and document analysis of assessment results. Research findings indicate that dysgraphia manifests in complex spectrum variations with different specific barriers in each individual. Assessment implementation using combination of formal instruments and direct observation produced complementary data illustrating that writing abilities fluctuate depending on learning contexts, with lower-grade students obtaining instrument scores of 51 in Sufficient category and observation scores of 32 in Good category, while upper-grade students demonstrated instrument scores of 62 and observation scores of 30 in Good category. Intervention strategies based on assessment results including fine motor exercises and structured writing therapy with 60% time allocation proved effective in improving writing abilities. Main challenges include limited learning media and minimal multi-stakeholder collaboration. Comprehensive assessment results serve as essential foundation for developing individual education programs tailored to specific needs of children with dysgraphia.   Abstrak Penelitian ini bertujuan mendeskripsikan dan menganalisis hasil penerapan asesmen anak disgrafia di Sekolah Dasar Negeri Sudimara Timur 2 sebagai sekolah penyelenggara pendidikan inklusi. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus deskriptif yang melibatkan dua siswa disgrafia dengan karakteristik berbeda dan satu guru pendidikan khusus sebagai informan kunci. Teknik pengumpulan data mencakup wawancara mendalam, observasi partisipatif, dan analisis dokumen hasil asesmen. Temuan penelitian menunjukkan bahwa disgrafia muncul dalam variasi spektrum yang kompleks dengan hambatan spesifik berbeda pada setiap individu. Implementasi asesmen menggunakan kombinasi instrumen formal dan observasi langsung menghasilkan data komplementer yang menggambarkan kemampuan menulis bersifat fluktuatif bergantung konteks pembelajaran, dengan siswa kelas rendah memperoleh skor instrumen 51 kategori Cukup dan observasi 32 kategori Baik, sedangkan siswa kelas tinggi menunjukkan skor instrumen 62 dan observasi 30 kategori Baik. Strategi intervensi berbasis hasil asesmen berupa latihan motorik halus dan terapi menulis terstruktur dengan alokasi waktu 60% terbukti efektif meningkatkan kemampuan menulis. Tantangan utama meliputi keterbatasan media pembelajaran dan minimnya kolaborasi multipihak. Hasil asesmen komprehensif menjadi landasan penting penyusunan program pendidikan individual yang sesuai kebutuhan spesifik anak disgrafia.   Kata Kunci: asesmen, disgrafia, pendidikan inklusi, program intervensi, sekolah dasar